Kvalitetslitterära debuter : En fallstudie om hur prisvinnande debutanter värderas på bokmarknaden - Haglund,Axel; Glaser,Emma (2022)
The aim of this analysis has been to investigate how the books Osebol (2019), Samlade verk (2020) and Eufori (2021) have been received and treated on the Swedish book market, while focusing on how these books are being associated with high-quality literature while at the same time being debut books. A case study has been carried out in four different time periods of these books’ lifespan, from admission at a publishing house to their respective August prize. The four analyzed periods are therefore: admission, publication, reception, and August prize. To analyze these four periods a set of interviews with each book’s respective publisher has been carried out, as well as an interview with the chairperson of the August prize jury. Each book’s first day review from Sweden’s five largest newspapers: Aftonbladet, Dagens Nyheter, Expressen, Göteborgs-Posten and Svenska Dagbladet have been analyzed with a text analysis method. Further has each book’s marketing material also been analyzed, this includes cover texts, press releases and portraits of the debutants in the magazine Svensk Bokhandel. Sales charts of each book has also been included in the study, as well at the August prize jury’s motivation for each book’s prize winning. Theories about capital, literary value, marketing, bestsellers, and paratexts have been used to guide the study and analyze its results. The result of the case study indicates that these three books have been treated differently on the book market, even though they are all debutants. Samlade verk was mentioned as a debutant the most out of the three books, and the other two were barely even mentioned as a debutant by their own publishing house. The three books were a lot more equal when it comes to what literary value that was bestowed upon them by all the different actors within the book market.
Keywords: osebol; samlade verk; eufori; värde; debut; Augustpriset